Penyuluhan Seks Bebas Di Yayasan Wasangkerta Dusun Karangdawa Kecamatan Setu Patok Cirebon Jawa Barat - Rachmawati, Diana Widhi; Mulyana, Yusep; PN, Trinandari; Zuliyana, Meti; Agustina, Juaidah; Permatasari, Nuryanti (PT. Cahya Edupreneur Indonesia, 2023)
Free sex is a complex social issue that affects various aspects of people's lives. Free sex behavior can have a significant negative impact on social development and health. The Wasangkerta Foundation in Karangdawa Hamlet, Cirebon, realizes the important role of education in overcoming the problem of free sex among teenagers and society. Counseling with the title